2021
DOI: 10.3390/mi12030262
|View full text |Cite
|
Sign up to set email alerts
|

Laser Grinding of Single-Crystal Silicon Wafer for Surface Finishing and Electrical Properties

Abstract: In this paper, we first report the laser grinding method for a single-crystal silicon wafer machined by diamond sawing. 3D laser scanning confocal microscope (LSCM), X-ray diffraction (XRD), scanning electron microscope (SEM), X-ray photoelectron spectroscopy (XPS), laser micro-Raman spectroscopy were utilized to characterize the surface quality of laser-grinded Si. Results show that SiO2 layer derived from mechanical machining process has been efficiently removed after laser grinding. Surface roughness Ra has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Monocrystalline silicon is the most popular substrate material used in the production of integrated circuits (IC) and is regarded as the foundation of many electronic devices [1][2][3]. Wafer surface quality is significant because it can enhance the performance and lifespan of IC devices [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Monocrystalline silicon is the most popular substrate material used in the production of integrated circuits (IC) and is regarded as the foundation of many electronic devices [1][2][3]. Wafer surface quality is significant because it can enhance the performance and lifespan of IC devices [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, laser processing, an alternative process of mechanical grinding, has received significant attention. Li et al 19 first reported the laser grinding method for a single-crystal silicon wafer machined by diamond sawing. In the report, they demonstrated that SiO 2 layer and Ra were reduced after femtosecond laser grinding.…”
mentioning
confidence: 99%